2017
DOI: 10.3390/ijgi6080249
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Impact of Meteorological Factors on Water Demand in the Las Vegas Valley Using Time-Series Analysis: 1990–2014

Abstract: Many factors impact a city's water consumption, including population distribution, average household income, water prices, water conservation programs, and climate. Of these, however, meteorological effects are considered to be the primary determinants of water consumption. In this study, the effects of climate on residential water consumption in Las Vegas, Nevada, were examined during the period from 1990 to 2014. The investigations found that climatic variables, including maximum temperature, minimum tempera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…The technique proposed in [19] utilizes a non-homogeneous Markov chain model, allowing for an understanding of the water consumption dynamics. This model can predict daily consumption patterns based on additional inputs, such as external factors like weather conditions [20], the day of the week, etc. A different study [21] concentrates on estimating water demand on a weekly and hourly basis using an autoregressive model that is based on a time-based periodic component of time series data to refine daily demand estimates and hours.…”
Section: Related Workmentioning
confidence: 99%
“…The technique proposed in [19] utilizes a non-homogeneous Markov chain model, allowing for an understanding of the water consumption dynamics. This model can predict daily consumption patterns based on additional inputs, such as external factors like weather conditions [20], the day of the week, etc. A different study [21] concentrates on estimating water demand on a weekly and hourly basis using an autoregressive model that is based on a time-based periodic component of time series data to refine daily demand estimates and hours.…”
Section: Related Workmentioning
confidence: 99%
“…Quevedo et al [32] assessed the effects of seasonal ARIMA (SARIMA) and exponential smoothing models that took calendar effects into account and showed that they were superior in forecasting water demand when temporal and daily periods were considered. Furthermore, Patcha et al [33] demonstrated that the ARIMAX model with dew point depression and average temperature input plays an important role in forecasting long-term water consumption rates in Las Vegas.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In fact, the approach proposed in [17] is based on a model of nonhomogeneous Markov chains allowing knowledge of the dynamics of water consumption. This model can predict behaviors of daily consumption based on other parameters such as exogenous factors represented by the climate [18], the day type, etc. Another study [19] deals with the water demand forecasting on weekly and hourly scales with an autoregressive model based on a periodic component on time series data to refine daily demand values and hours.…”
Section: Forecasting With Machine-learning Algorithmsmentioning
confidence: 99%